New inflammatory markers associated with disease activity in rheumatoid arthritis: pan-immune-inflammation value, systemic immune-inflammation index, and systemic inflammation response index - İpek Okutan; Recai Aci; Âdem Keskin; Melek Bilgin; Halit Kızılet (Rheumatology)
Introduction This study aimed to investigate the relationship between the pan-immune-inflammation value (PIV), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI) and disease activity in rheumatoid arthritis (RA), characterized by chronic inflammation and immune system involvement, and to provide new insights into the clinical implications of RA.